Cryopreserved platelets in bleeding management in remote hospitals: A clinical feasibility study in Sweden - Wikman, Agneta; Diedrich, Beatrice; Björling, Karl; Forsberg, Per-Olof; Harstad, Anna-Maria; Henningsson, Ragnar; Höglund, Petter; Sköld, Hans; Östman, Lars; Sandgren, Per (Frontiers in Public Health, 2023)
Background: In bleeding patients balanced transfusions, including platelets are critical to ensure hemostasis. Many rural hospitals have no or limited platelet inventory, with several hours transport time from larger hospitals. The aim of this study was to evaluate the feasibility of using cryopreserved platelets that can be stored for years, in remote hospitals with no or limited platelet inventory. Material and Methods: Three remote hospitals participated in a prospective study including adult bleeding patients where platelet transfusions were indicated. Cryopreserved platelets were prepared in a university hospital, concentrated in 10 mL, transported on dry ice and stored in -80oC at the receiving hospital. At request the concentrated platelet units were thawed and suspended in fresh frozen plasma. A subjective assessment of the clinical effect was done by the treating anesthetist and surgeon. Blood transfusion needs and laboratory parameters pre- and posttransfusion as well as the logistics, including time and work efforts, were evaluated. Results: Twenty-three bleeding patients were included. Nine (39%) of the patients were treated due to gastrointestinal bleeding, five (22%) due to perioperative bleeding and four (17%) due to trauma bleeding. The transfusion need were 4.9+3.3 red blood cell units, 3.2+2.3 plasma units and 1.9+2.2 platelet units, whereof cryopreserved 1.5+1.1 (mean+SD). One patient had a mild allergic reaction. We could not show difference in laboratory results pre- and posttransfusion of the cryopreserved units in the bleeding patients. The mean time from order of platelets to transfusion was 64 minutes, with a range from 25 to 180 minutes. Conclusion: Cryopreserved platelets in remote hospitals are logistically feasible and of importance in emergency preparedness. The ability to have platelets in stock may increase the possibility to ensure hemostasis and improve survival in bleeding patients. In addition, cryopreserved platelets may be useful as a back-up inventory in large hospitals and blood establishments.